ASSOCIATION BETWEEN HIV KNOWLEDGE AND RISK BEHAVIOR IN PERSONS WHO INJECT DRUGS IN THAI NGUYEN, VIETNAM - Lim, Travis W. (Southeast Asian J Trop Med Public Health, 2014)
In Vietnam, HIV infection is concentrated in key populations including persons who inject drugs (PWID). The majority of PWID can name specific transmission routes of HIV, yet risk behaviors remain high. We conducted a cross-sectional survey of 1355 PWID in Thai Nguyen Province, Vietnam, to and compare their HIV knowledge with their self-reported risk behavior. Broader knowledge of HIV transmission, measured by a higher composite HIV knowledge score, was associated with a 19.5% lower adjusted odds of giving a used needle to another (p=0.011), and 20.4% lower adjusted odds of using a needle that another had used (p=0.001). A higher knowledge score was associated with 13.1% higher adjusted odds of consistent condom use (p=0.083). These results suggest a broader knowledge may reflect characteristics about how individuals obtain knowledge or the way that knowledge is delivered to them, and may be associated with their ability to engage in risk reduction behavior.